The Influence of Accountability and Transparency on Budget Performance With The Concept of Value For Money in The Lumajang District Government - Sukma Uli Nuha (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The purpose of this study was to determine the effect of accountability and transparency on budget performance with the concept of value for money at the Lumajang District Government. The type of research used is causal associative research, namely analysis that aims to understand the causal relationship, data collection by interviewing and distributing questionnaires to respondents. Purposive sampling technique and this research data is processed using SPSS (Statistica Product and Service Solution) software with data analysis testing, classical assumption test and hypothesis testing. The conclusion of this study is that partially accountability and transparency have a positive and significant effect on budget performance with the concept of value for money. In hypothesis testing there is a positive and significant effect, and simultaneously between accountability and transparency together have an effect on budget performance with the concept of value for money. Based on the research results, the advice given to the Lumajang Regency government is to be able to create accountability and maintain accountability and transparency on budget performance.